Pemanfaatan Program Primavera 6.0 Sebagai Efisiensi Pelaksanaan Pekerjaan (Studi Kasus: Penambahan Bangunan Pelengkap Dan Alat Hidromekanikal Bendungan Bintang Bano Di Kabupaten Sumbawa Barat) - Muhibbin, Ikhwanul; Hariyadi, Hariyadi; Hamdani, Hafiz; Samengasbumi, Ringgi Puteri (Universitas Pahlawan Tuanku Tambusai, 2024)
In the modern era like today, development projects are developing rapidly. In a development project, several problems often occur that can hinder project completion. Problems that occur are often caused by the level of difficulty and complexity of each work carried out. Therefore, the Primavera 6.0 program can be used to improve performance in project completion. The problem itself can be overcome by accelerating the addition of labor and working time. This research uses a project to add additional buildings and hydromechanical equipment to the Bintang Bano Dam in West Sumbawa Regency. This research aims to obtain efficiency in project implementation, therefore a work network analysis was carried out using the PDM (Precedence Diagram Method) strategy to obtain critical work and the crashing method to obtain acceleration duration using Primavera 6.0 software as a tool. From this analysis, critical work was found in the cliff safety sub-work (shotcrete) and the construction of stop log houses. The efficiency obtained from accelerating critical work is the result of accelerating by adding workers who get 24 days less than the normal time. As a result of the acceleration carried out, the total project cost was initially Rp. 10,600,900,901.24 in 224 days to Rp. 10,549,232,260.12 in 200 days, there is a difference of Rp. 51,668,641.11 from the normal project or a decrease of 0.49%. Meanwhile, acceleration was carried out by adding working time (overtime) to get 19 days shorter than normal time. As a result of the acceleration carried out, the total project cost was initially Rp. 10,600,900,901.24 in 224 days to Rp. 10,590,687,924.51 in 205 days, there is a difference of Rp. 10,212,976.73 from the normal project or a decrease of 0.10%.